OTHERNESS IN I, TITUBA BLACK WITCH… OF SALEM BYMARYSE CONDÉ ET MASTERS OF THE DEW BY JACQUES ROUMAIN - (:unkn) unknown (My University, 2019)
OTHERNESS IN I, TITUBA BLACK WITCH… OF SALEM BYMARYSE CONDÉ ET MASTERS OF THE DEW BY JACQUES ROUMAINThis work is a study of the representation of Otherness as a theme in I, Tituba Black Witch… of Salem by Maryse Condé and Masters of the Dew by Jacques Roumain. The study was however done using the French versions of the two novels. The study raises the difficulties of Self/Other relationship of individuals, post-independent African countries with specific reference to the Caribbean and the descendants of slavery in Africa. Literature proves that imperialism, colonization, slavery, slave trade, patriarchy, racism, inferiority and superiority complex, domination and politics of exclusion by the dominant groups on the dominated groups among others are the factors that give rise to Otherness as represented in the fictional works of these two Negro-African writers of French Expression. The means by which Self/Other relationship manifests itself are through the politics of exclusion, hate speech, deprivation, exploitation of the Other etc. Orchestrators of Otherness consciously extort, torture and exploit their victims for their personal gains. Their actions on the victims have nefarious effects such as the deprivation of one’s liberty, killings, sexual and moral harassment, stigmatization, and marginalization of the Other, cultural inferiority among others. The work also denounces the complicity and conspiracy of the West, the African brothers, the slave traders, families, men, and all the dominant classes in the exaltation of the negative side of Otherness. It is within this framework that our research begins. Starting with the origins or causes of Otherness in the first place, followed by the inevitable effects of this cataclysm. Postcolonial theory and that of the feminism as a theory are the theoretical approaches or analytical tools employed by this study to analyze the representation of Otherness in I, Tituba Black Witch…of Salem and Masters
Keywords: African Research